Squalus acanthias, spiny dogfish - Finucci, B.; Cheok, J.; Chiaramonte, Gustavo Enrique; Cotton, C. F.; Dulvy, N. K.; Kulka, D. W.; Neat, F. C.; Pacoureau, N.; Rigby, C. L.; Tanaka, S.; Walker, T. I.
While there are reported subpopulations of Squalus acanthias (Linnaeus, 1758) elsewhere in the world, the North Pacific subpopulation is now considered a separate species, Squalus suckleyi (Girard, 1854) (see Ebert et al. 2010). Further taxonomic studies on this genus are required, including in relation to Mediterranean and Black Sea subpopulations. In Europe, three subpopulations are inferred to occur. Fil: Finucci, B. National Institute of Water and Atmospheric Research; Nueva Zelanda Fil: Cheok, J. University Fraser Simon; Canadá Fil: Chiaramonte, Gustavo Enrique. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia". Estación Hidrobiológica de Puerto Quequén (sede Quequén); Argentina Fil: Cotton, C. F. Florida State University; Estados Unidos Fil: Dulvy, N. K. University Fraser Simon; Canadá Fil: Kulka, D. W. No especifíca; Argentina Fil: Neat, F. C. No especifíca; Argentina Fil: Pacoureau, N. University Fraser Simon; Canadá Fil: Rigby, C. L. James Cook University; Australia Fil: Tanaka, S. No especifíca; Argentina Fil: Walker, T. I. University of Melbourne; Australia